APLIKASI BIOTEKNOLOGI MOLEKULER DALAM BUDAYA PERAIRAN - Indyaswan Tegar Suryaningtyas (OSEANA, 2017)
MOLECULAR BIOTECHNOLOGY APPLICATION IN MARINE AQUACULTURE. Aquaculture industry, as a promising solution for the decrease of natural broodstock as well as an important part in people's health and economics, has been growing rapidly. Biomolecular technologies are now used as a base for proper management of aquaculture programs. Those technologies include breeding program with genetic maps; mono-sex aquaculture program to maximize production's effectiveness; transgenic program; and pathogen's early detection using bio-molecular methods. it can be said that the modern aquaculture industry nowadays depends on the application of molecular biotechnology with support from better aquaculture-system management for product organization.